2002
DOI: 10.1007/s00439-002-0777-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 7p disruptions in Silver Russell syndrome: delineating an imprinted candidate gene region.

Abstract: Silver-Russell syndrome (SRS) is characterised by pre- and postnatal growth restriction (PNGR) and additional dysmorphic features including body asymmetry and fifth finger clinodactyly. The syndrome is genetically heterogeneous, with a number of chromosomes implicated. However, maternal uniparental disomy for chromosome 7 has been demonstrated in up to 10% of all cases. Three SRS probands have previously been described with a maternally inherited duplication of 7p11.2-p13, defining this as a candidate region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 45 publications
0
54
0
5
Order By: Relevance
“…In addition, the duplication of pre-existing pathogenic mutations by isodisomy can lead to the clinical expression of recessive disorders (such as cystic fibrosis) in patients with upd(7)mat [38][39][40] . Candidate SRS regions have been suggested through identification of patients with segmental upd(7)mat or CNVs (see Supplementary information S3 (table)); the primary candidate SRS genes on chromosome 7 are currently GRB10 (7p12.1) and MEST (7q32) [41][42][43][44][45][46][47][48] . Microsatellite analysis was the first diagnostic test for upd(7)mat 35,36 ; however, this analysis cannot detect imprinting defects (epimutations) and requires DNA from at least one parent.…”
Section: Chromosomementioning
confidence: 99%
“…In addition, the duplication of pre-existing pathogenic mutations by isodisomy can lead to the clinical expression of recessive disorders (such as cystic fibrosis) in patients with upd(7)mat [38][39][40] . Candidate SRS regions have been suggested through identification of patients with segmental upd(7)mat or CNVs (see Supplementary information S3 (table)); the primary candidate SRS genes on chromosome 7 are currently GRB10 (7p12.1) and MEST (7q32) [41][42][43][44][45][46][47][48] . Microsatellite analysis was the first diagnostic test for upd(7)mat 35,36 ; however, this analysis cannot detect imprinting defects (epimutations) and requires DNA from at least one parent.…”
Section: Chromosomementioning
confidence: 99%
“…1 As inferred earlier, mitochondrial disorders can manifest in various phenotypic classifications. We see in Tables 1 and 2 that MRP genes are candidates for dwarfism, growth retardation, and limb deformity disorders such as Russell-Silver Syndrome, 49,50 Stuve-Wiedemann Syndrome, 51 and Moebius Syndrome I. 52 Metabolic disorders for which MRP genes associate by map position are Multiple Mitochondrial Dysfunctions, 53 Stuve-Wiedemann Syndrome, 51 Leigh Syndrome, 54 and diabetes.…”
Section: Mrp Characterization Gene Identification and Mappingmentioning
confidence: 99%
“…14 The role of genomic imprinting in IUGR pregnancies has been investigated, but systematic studies are sparse. 15,16 A recent study comparing gene expression profiles of normal and IUGR placentas using microarrays which included 27 imprinted genes demonstrated that 22% of the imprinted genes were differentially expressed, far in excess of the non-imprinted genes. 7 These results strongly demonstrate a critical role of genomic imprinting in placental/fetal growth and suggest that IUGR may be a result of altered expression of critical imprinted genes.…”
Section: Introductionmentioning
confidence: 99%